The Multiple Meanings of a Flowchart. - Ensmenger, Nathan (Information & Culture, 2016)
From the very earliest days of electronic computing, flowcharts have been used to represent the conceptual structure of complex software systems. In much of the literature on software development, the flowchart serves as the central design document around which systems analysts, computer programmers, and end users communicate, negotiate, and represent complexity. And yet the meaning of any particular flowchart was often highly contested, and the apparent specificity of such design documents rarely reflected reality. Drawing on the sociological concept of the boundary object, this article explores the material culture of software development with a particular focus on the ways in which flowcharts served as political artifacts within the emerging communities of practices of computer programming.